Environmental, Social, and Economic Benefits of Rooftop Farming - Pokhrel, Urmila; Giri, Koshila; Chaudhary, Subheksha; Rajbhandari, Binayak P. (Nepalese Journal of Agricultural Sciences, 2025)
Rooftop farming has emerged as a transformative solution to address pressing urban challenges in Kathmandu, Nepal, amidst rapid urbanization and population growth. This paper explores the historical roots, types, benefits, and economic insights of rooftop farming, focusing on its significance in Kathmandu’s urban landscape. Drawing on historical examples and contemporary initiatives, the study highlights the multifaceted benefits of rooftop farming, including environmental sustainability, food security, community resilience, and economic empowerment. By examining the successes and challenges of rooftop farming in Kathmandu, this paper underscores its potential as a sustainable urban agricultural practice and calls for concerted efforts to mainstream and scale up rooftop farming initiatives in Kathmandu and beyond.